Shariah-Compliant Equity Liquidity - A Systematic Review of Concepts, Methods, and Empirical Findings - Sri Marlia; Isti Nuzulul Atiah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2025)
One of the most important criteria for assessing equities in the capital market is liquidity, which investors take into account when choosing which investments to make. However, restrictions based on Islamic principles are frequently linked to possible decreases in liquidity in the context of Islamic capital markets because of issuer leverage levels and sector constraints. This study uses a systematic literature review approach to map the evolution of research on Islamic stock liquidity. Using inclusion criteria that restrict the selection to journal articles focusing on Islamic equities, liquidity or market-quality dimensions, available in English or Indonesian, and offering empirical or conceptually relevant insights, 30 Scopus-indexed articles published between 2010 and 2025 were selected. The results indicate that market microstructure, resilience, indirect liquidity factors, and linkages between liquidity and volatility are receiving more scholarly attention. Shariah screening and structural market characteristics give Shariah-compliant stocks their partial safe-haven qualities, higher volatility resistance, and stable price-adjustment mechanisms, despite their generally reduced liquidity.